The Fundamental Concept of Islamic Education Perspective K.H. Hasyim Asy'ari - Jihan Jihan; Wiwin Rif'atul Fauziyati; Nova Krisnawati (Universitas Majalengka, 2023)
The basic concept of Islamic education has emerged along with the emergence of Islam in the world. The Qur'an as a source of knowledge became a different motivator for Muslim intellectuals in the Middle age, so Islam developed rapidly in the century. Along the times, many basic concepts of Islamic education were born; one was from K.H Hasyim Asy'ari: a Kiai and a big figure in the freedom fight. By referring to the Qur'an and Hadith, he emphasized that the basis of Islamic education aims to create perfect humans. He described the concept of Islamic education clearly in several of his books. This study uses a qualitative method of library research, which aims to describe the basic idea of Islamic education from the perspective of K.H Hasyim Asy'ari, which is widely revealed in several of his books, one of them is Adabul 'Alim wa Muta'allim. Library research is the study research that utilizes library data as a data source. Thus, to find out in detail his concept of education, which is focused on not only religious education such as the study of the interpretation of the Qur'an, hadith, ushuluddin, books of the madhhab fiqh, nahwu, Musharraf, and material that discusses Sufism but also studies general, adapted to the times.